Metabolic and Transcriptional Changes in Cultured Muscle Stem Cells from Low Birth Weight Subjects - Hansen, Ninna S.; Hjort, Line; Broholm, Christa; Gillberg, Linn; Schrölkamp, Maren; Schultz, Heidi. S.; Mortensen, Brynjulf; Jørgensen, Sine W.; Friedrichsen, Martin; Wojtaszewski, Jørgen F. P.; Pedersen, Bente K.; Vaag, Allan (The journal of clinical endocrinology and metabolism, 2016)
Context/Objective:Developmental programming of human muscle stem cells could in part explain why individuals born with low birth weight (LBW) have an increased risk of developing type 2 diabetes (T2D) later in life. We hypothesized that immature muscle stem cell functions including abnormal differentiation potential and metabolic function could link LBW with the risk of developing T2D.Design/Settings/Participants:We recruited 23 young men with LBW and 16 age-matched control subjects with normal birth weight. Biopsies were obtained from vastus lateralis, and muscle stem cells were isolated and cultured into fully differentiated myotubes.Main Outcome Measures:We studied glucose uptake, glucose transporters, insulin signaling, key transcriptional markers of myotube maturity, selected site-specific DNA methylation, and mitochondrial gene expression.Results:We found reduced glucose uptake as well as decreased levels of glucose transporter-1 and -4 mRNA and of the Akt substrate of 160-kDa mRNA and protein in myotubes from LBW individuals compared with normal birth weight individuals. The myogenic differentiation markers, myogenin and myosin heavy chain 1 and 2, were decreased during late differentiation in LBW myotubes. Additionally, mRNA levels of the peroxisome proliferator-activated receptor-γ coactivator-1α and cytochrome c oxidase polypeptide 7A were reduced in LBW myotubes. Decreased gene expression was not explained by changes in DNA methylation levels.Conclusion:We demonstrate transcriptional and metabolic alterations in cultured primary satellite cells isolated from LBW individuals after several cell divisions, pointing toward a retained intrinsic defect conserved in these myotubes.